Protocolo de análisis para el control de la bacteria Listeria Monocytógenes en puré de banano acidificado sin semillas que se producen en Industrias Borja INBORJA en el tercer trimestre del año 2013 - Peláez Morocho, Paúl A. (2014)
The increase for food (TEF) borne disease has become a public health problem. The bacterium Listeria monocytógenes is responsible for, the etiologic agent of Listeriosis or typical food poisoning is considered one of the most important diseases among foodborne diseases.